A primer on sleep for MFTs: Implications and practical considerations. (12th May 2021) - Novak, Joshua R.; Gillis, Brian T.
Abstract: Despite many marriage and family therapists (MFTs) utilizing the Biopsychosocial‐Spiritual (BPSS) framework in assessment and treatment, there is still a lack of education on sleep and the implications for mental, emotional, and relational health. Newer research within many fields highlights the far‐reaching spillover effects of short or poor‐quality sleep that can affect our clients. MFTs need to know how to assess, how to provide proper psychoeducation, how to apply this knowledge in clinical settings, and how to collaborate with other healthcare providers. As such, the purpose of this article is threefold: (a) review the biopsychosocial‐spiritual importance of sleep; (b) equip MFTs with information on sleep assessment, how to identify situations for referral, and how to provide psychoeducation on sleep hygiene; and (c) review important considerations for research and practice for MFTs.